2020
DOI: 10.1371/journal.pone.0228586
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to treatment for polycystic ovarian syndrome: A systematic review

Abstract: Background Polycystic ovarian syndrome (PCOS) is one of the most prevalent endocrine disorders of women of reproductive age. Treatment plans for this chronic condition frequently include long-term use of a combination of medication and lifestyle interventions. However, treatment outcomes are dependent on adherence to treatment regimens. This study aimed to systematically review the literature for reported adherence to treatments for PCOS. Methods A systematic search of Embase, Cochrane, PubMed, CINAHL, PsychIN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…88 A review of studies in PCOS involving lifestyle intervention did not provide significant data on adherence to the programs in the majority of trials. 89 A detailed look at 4 randomized trials of lifestyle intervention in PCOS involving a total of 221 women showed attrition from the programs was 47.1%. However, weight loss of >5% occurred in 63% of the women.…”
Section: Meta-analysis Of Lifestyle Interventionsmentioning
confidence: 99%
“…88 A review of studies in PCOS involving lifestyle intervention did not provide significant data on adherence to the programs in the majority of trials. 89 A detailed look at 4 randomized trials of lifestyle intervention in PCOS involving a total of 221 women showed attrition from the programs was 47.1%. However, weight loss of >5% occurred in 63% of the women.…”
Section: Meta-analysis Of Lifestyle Interventionsmentioning
confidence: 99%
“…Zingiber officinale Roscoe (ginger) from the family of Zingeiberaceae family lowers serum levels in fasting glucose, insulin, low-and high-density lipoprotein-cholesterols 21 . PCOS is connected with T2DM through obesity and insulin resistance and lower serum levels can lowers the disease 22 . Liao et al 23 performed herbs and herbal treatment in PCOS women through Jia-Wei-Xiao-Yao-San and Xing-Fu; were commonly used herb and these showed the positiveness towards the treatment in Taiwanese PCOS women.…”
Section: Introductionmentioning
confidence: 99%
“…The standard treatment for PCOS addresses the menstrual irregularity and hyperandrogenism with oral contraceptive pills. At the same time, the metabolic features are managed with metformin, a drug used to reduce the blood sugar levels in T2DM patients [ 5 ]. Though these drugs are effective, the medication must still be taken regularly and may present mild to severe side effects.…”
Section: Introductionmentioning
confidence: 99%